Perfectionism and burnout in sport and dance - Skwiot, M.; Sliwinski, Z.; Sliwinski, G. E. (Physikalische Medizin - Rehabilitationsmedizin - Kurortmedizin, 2020)
Objectives The aim of the present study was to evaluate the interaction between perfectionism and symptoms of burnout in athletes and dancers and examine the influence of chronic musculoskeletal pain on burnout levels.